Karakter Agronomi dan Fisiologi Varietas Cabai Merah pada Kondisi Cekaman Genangan - , Susilawati; Rujito Agus Suwignyo; , Munandar; Mery Hasmeda (Indonesian Journal of Agronomy, 2012)
The research objective was to study the agronomic and physiological characteristics of red chilli (Capsicum annuumL.) varieties under waterlogging stress. These studies were conducted at two locations: in Palembang, South Sumatra, from February to August 2010 and in Bogor in West Java, from September to November 2010. Experiments in Palembang was using split plot design with three replications. The main plot was waterlogging treatment for 1, 2, 3 and 4 days. The subplot was red chilli varieties: Kiyo F1, Riawan, Ferosa, Bravo F1 and Laris. Experiments in Bogor was conducted without the use of experimental design; the same plant varieties were waterlogged for 2 and 4 days. The results showed that waterlogging caused root damages on all varieties. Kiyo F1 had better agronomic characters and high levels of tolerance than other varieties. The content of ethylene in all varieties increased with increasing time of waterlogging, except for Laris. In all varieties both leaf chlorophyll and tissue N content tend to decline with the increase in waterlogging duration. However Bravo F1 experienced an increase in the chlorophyll content whereas Kiyo F1 had an increase in N in the plant tissue. Keywords: agronomic character, physiological character, red chili, waterlogging